Susan Folkman’ elaborated (enlarged) classical model of stress and coping. On a role and meaning of positive emotions - Gruszczyńska, Ewa (Studia Psychologica: Theoria et praxis, 2007)
So far the great majority of empirical studies have focused on form and function of negative emotions during stressful transaction, probably because of both their immanent presence and strong effects. Recently, this concern has been shifted to the aspects of positive emotions’ role in the coping process, yet unaddressed. Important findings, resulting strictly from classical Lazarus’s research, showed that people reported mixed feelings in the face of difficulties. Thus, positive emotions co-occur with distress. Lately, Folkman has shed light on how people can generate and use positive affect to sustain coping, even in the conditions almost derived of the possibility for personal control and satisfactory outcome. Three types of such strategies have been distinguished: positive reappraisal, problem-focused coping concentrated on “what can be done” and creation of positive events. Together, as a meaningfocused coping, they expand the classical stress model into promising new areas of coping research.